Exploring the Use of Pegylated Liposomal Doxorubicin (Caelyx®) as Pressurized Intraperitoneal Aerosol Chemotherapy - Robella, Manuela; Vaira, Marco; Argenziano, Monica; Spagnolo, Rita; Cavalli, Roberta; Borsano, Alice; Gentilli, Sergio; De Simone, Michele (Frontiers in Pharmacology, 2019)
Background: Peritoneal carcinomatosis is a common metastatic pattern in ovarian, gastric, colorectal, and appendiceal cancer; systemic chemotherapy is the current standard of care for peritoneal metastatic disease; however, in a subset of patients its beneficial effect remains questionable. More effective perioperative chemotherapy is needed. Materials and methods: Pressurized intraperitoneal aerosol chemotherapy (PIPAC) is a new treatment that applies chemotherapeutic drugs into the peritoneal cavity as an aerosol under pressure. It’s a safe and feasible approach that improves local bioavailability of chemotherapeutic drugs as compared with conventional intraperitoneal chemotherapy. Till now the drugs used in PIPAC for the treatment of the peritoneal carcinomatosis (PC) are cisplatin, doxorubicin, and oxaliplatin; as of yet, there are no in vivo data comparing different drug formulations and dosage schedules of PIPAC. Pegylated liposomal doxorubicin 1.5 mg/sm was aerosolized in PIPAC procedures. Results: Pharmacokinetics analysis of 10 procedures performed with conventional doxorubicin solution at the dose of 1.5 mg/m2 were compared to 15 procedures with the same dose of pegylated liposomal doxorubicin (PLD). Significant differences between experimental groups were detected by one-way ANOVA followed by Bonferroni correction; a p value < 0.05 was considered statistically significant. A statistically different doxorubicin tissue concentration was observed for the doxorubicin solution compared to pegylated liposomal doxorubicin in the right parietal peritoneum and right diaphragm. In the Caelyx® series a mean tissue concentration of 1.27 ± 1.33 mg/g was reported, while in the second one we registered a mean concentration of 3.1 ± 3.7 mg/g. Conclusions: The delivery of nano-particles in PIPAC was feasible, but pegylated liposomal concentrations are lower than standard doxorubicin formulation. Probably mechanical and physical properties of pressurized aerosol chemotherapy might alter their stability and cause structural disintegration.